AIAA Atmospheric Flight Mechanics Conference 2015
DOI: 10.2514/6.2015-2243
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Feedforward Control Design for Gust Loads Alleviation of Highly Flexible Aircraft

Abstract: When prior knowledge of the plant controlled is available, feedforward control is preferred over feedback control for disturbance rejection. The stability characteristics of the system using feedforward control are the same as the original plant. Adaptive feedforward control design for gust loads alleviation of both a two degrees of freedom aerofoil with polynomial structural nonlinearity and a free flying flexible aircraft with large geometric wing deformations is investigated. Two dimensional thin aerofoil t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The last objective assesses the effects of the proposed controller for GLA. It is worth noting that a follow-up study conducted flight tests on a high-altitude, longendurance unmanned air vehicle with a wing span of 24 m [19]. The paper continues with a description of the aeroelastic testbed in Section 2.…”
Section: Aeroelastic Modelmentioning
confidence: 99%
“…The last objective assesses the effects of the proposed controller for GLA. It is worth noting that a follow-up study conducted flight tests on a high-altitude, longendurance unmanned air vehicle with a wing span of 24 m [19]. The paper continues with a description of the aeroelastic testbed in Section 2.…”
Section: Aeroelastic Modelmentioning
confidence: 99%
“…While some parameters causing these variations are known, it is difficult to precisely model their effect on the various aeroelastic modes that compose the system. The main approach to deal with this important issue in GLA is to define adaptive control laws, generally relying on finite-impulse response controllers [9][10][11][30][31][32], that can adapt in real-time to the current system thanks to the sensors' measurements. This technique is promising but requires an on-line optimization process that can be computationally intensive and does not lead to strong guarantees of stability and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Flight-test measurements showed that the designed Lidar system was potential for future implementation in a real-time feedforward flight control system. The work of [35][36][37] investigated the gust load alleviation (GLA) problem using Lidar preview measurements of the incoming gust, based on model predictive control, gain-scheduled linear parametervarying control and adaptive feedforward control, respectively. Their simulation results showed that the wing root bending moments and the average vertical acceleration were largely reduced, indicating better load alleviation performance and disturbance rejection performance.…”
Section: Introductionmentioning
confidence: 99%